Pengaruh Skeptisisme Profesional dan Beban Kerja Auditor Internal Pemerintah terhadap Pendeteksian Kecurangan di Sektor Publik : (Studi pada Perwakilan BPKP Provinsi Nusa Tenggara Timur) - Angelia Trisna Beka; Herly M. Oematan; Minarni A. Dethan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of professional skepticism and workload of government internal auditors on fraud detection at the BPKP Representative of East Nusa Tenggara Province. The data used in this study were obtained using a questionnaire. This study uses a quantitative descriptive research approach. The population and sample in this study were all auditors at the BPKP Representative of East Nusa Tenggara Province. The sampling method in this study used purposive sampling method. The analysis method used is descriptive statistical analysis, validity test, reliability test, classical assumption test, multiple linear regression and hypothesis testing using the help of the statistical package for the social sciences 27 (SPSS 27) application. The results of this study state that professional skepticism affects fraud detection. Workload affects fraud detection. Professional skepticism and workload variables simultaneously affect fraud detection.